TRADE PROMOTION AND SALES VOLUME: THE MEDIATING ROLE OF DISTRIBUTOR MARKETING PERFORMANCE - Muhammad Fadli Hasballah; Nurainun; Syamsul Bahri; Mariyudi; Ikramuddin; Heriyana (RADJA PUBLIKA, 2026)
This study examines the influence of sales contest, promotion policy, and distributor salesperson incentives on sales volume, withdistributor marketing performance serving as a mediating variable. The research utilized a probability sampling method with a census approach, involving all 180 official distributors of PT Pupuk Iskandar Muda as respondents. Data were analyzed using the SEM-PLS technique through SmartPLS 4.0. The results reveal that distributor salesperson incentives and distributor marketingperformance significantly affect sales volume, whereas sales contest shows no significant impact. Promotion policy does not directly influence sales volume but demonstrates a significant effect on distributor marketing performance. Furthermore, distributor marketing performance is confirmed to mediate the relationship between promotion policy and distributor salesperson incentives on sales volume. These findings highlight the crucial role of distributor marketing effectiveness in strengthening the impact of incentive-based strategies, offering important managerial insights for optimizing distribution performance and enhancing market penetration.